2017
DOI: 10.1039/c6gc03200a
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced radical-initiated carboxylative cyclization of allyl amines with carbon dioxide

Abstract: A highly efficient photoinduced radical-initiated strategy for the carboxylative cyclization of allyl amines with CO2 was developed firstly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(32 citation statements)
references
References 42 publications
1
30
0
1
Order By: Relevance
“…Products of both reactions were also manipulated to give open-chain compounds. He and co-workers demonstrated that, in the presence of 1,5,7-triazabicyclo[4,4,0]dec-5-ene TDB as the base, the metal catalyst is unnecessary with perfluoroalkyl halides [171]. They carried out some experiments to elucidate the mechanism and from the evidence they proposed the mechanism depicted in Scheme 19.…”
Section: Scheme 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Products of both reactions were also manipulated to give open-chain compounds. He and co-workers demonstrated that, in the presence of 1,5,7-triazabicyclo[4,4,0]dec-5-ene TDB as the base, the metal catalyst is unnecessary with perfluoroalkyl halides [171]. They carried out some experiments to elucidate the mechanism and from the evidence they proposed the mechanism depicted in Scheme 19.…”
Section: Scheme 13mentioning
confidence: 99%
“…• the first one involved the formation of cyclic carbonate by the classical mechanism (see Scheme 2), then amine opened the carbonate by releasing of diol and formation of a isocyanate, which in turn added another molecule of epoxide (path a); • the second one involved the interaction between the cyclic carbonate and the amino-alcohol from nucleophilic opening of epoxide by amine(path b). The N-heterocyclic carbene copper and silver complexes supported on graphene or nanotubes, introduced by Chen and co-workers (see also He and co-workers demonstrated that, in the presence of 1,5,7-triazabicyclo [4,4,0]dec-5-ene TDB as the base, the metal catalyst is unnecessary with perfluoroalkyl halides [171]. They carried out some experiments to elucidate the mechanism and from the evidence they proposed the mechanism depicted in Scheme 19.…”
Section: Scheme 13mentioning
confidence: 99%
“…In 2017, an elegant visible‐light‐driven carboxylative cyclization reaction of allylamines with CO 2 under metal‐free conditions was reported by the He group (Scheme ) . In this transformation, perfluoroalkylated oxazolidin‐2‐ones were obtained with high efficiencies under mild conditions by using perfluoroalkyl iodides as the radical source.…”
Section: Cyclization Reactions Of Allylic Homoallylic and Benzylic mentioning
confidence: 99%
“…In 2017, an elegant visible-light-driven carboxylative cyclization reaction of allylamines with CO 2 under metal-free conditions was reported by the He group (Scheme 32). [49] In this transformation, perfluoroalkylated oxazolidin-2-ones wereo btained with high efficiencies under mild conditions by using perfluoroalkyli odides as the radical source.I nitiated by visible light, perfluoroalkyl iodides, such as nC 4 F 9 I, underwent homolytic Scheme28. Synthesis of oxazolidin-2-ones through the direct introduction of CO 2 into allylamine derivatives.…”
Section: Visible-light-driven Cyclizationr Eactionsmentioning
confidence: 99%
“…Fluorine containing carbonates can be synthesized via direct fluorination,, electrochemical fluorination, halogen exchange reaction, carbonation and others ,. Out of those, the carbonation of oxiranes as a chemical fixation of carbon dioxide represents a green and sustainable route to five‐membered cyclic carbonates, since it is a solvent‐free process employing moderate temperatures and pressures and is a viable alternative to toxic phosgene …”
Section: Introductionmentioning
confidence: 99%